Tingkat Kesejahteraan Petani Karet Di Nagari Padang Ganting Kabupaten Tanah Datar - Putri, Lusi Aulia; Bakaruddin, Bakaruddin; Nefilinda, Nefilinda (STKIP PGRI Sumbar, 2013)
Rubber farming communities in Nagari Padang Ganting in Tanah Datar generally oriented to the rubber farmers whose results sometimes income decreased, and many farmers are complaining, because they are still difficulties in meeting their daily needs, housing that does not meet the terms of a healthy home, and does have good clothes, cannot get good clothes, cannot get a decent education, the role of father, mother and child are not efficient and the relationship between individuals in poor families, and the community is also looking for a second job. It is expected, among others, due to weather conditions. The aims of research is to describe the Rubber Growers Welfare Nagari Padang Ganting in Tanah Datar in view of the economic conditions, the condition of education, health conditions and conditions in the family interaction. This research is a descriptive study. The population in this study were all heads of farm families in Nagari Padang Ganting in Tanah Datar. So there is a sample of the total population in the region amounted to 750 households, while the sampling technique with proportional random sampling of respondents, with a proportion of 10 % of the obtained number 75 KK / respondent. Research data collection use a questionnaire with data analysis using the percentage formula. The results of the four variables showed that: 1). Economic conditions are still relatively low in view of the basic income of farmers rubber < Rp375.000/minggu as much as 74.67 % of respondents, 2). Conditions formal education is already high rubber farmers graduated from high school as much as 45.33 % of respondents and non-formal education is a field exerting followed by 48 % of respondents, 3). Health conditions seen from illness last year was cold and fever as much as 41.33 % of respondents, and 4). Interaction in the highest family is childs interactions with the child (the attitude of his fellow child) are loving each other as much as 98.67 % of respondents.